Learner readiness and efficiency of learning English in online higher education Context: Voices of Turkish EFL learners - TOMAK, BURAK (My University, 2023)
Today, online education has become indispensable for many learning environments, including those designated for teaching and learning languages, becoming widespread and revolutionizing how students access education and language learning resources. This shift to online platforms has opened up numerous opportunities for learners, breaking down barriers of distance and time constraints. However, it also brings challenges, especially in the Turkish context. From this perspective, this study aimed to determine the online readiness of Turkish learners of English and the factors affecting the (in)efficiency of their online language education in their universities. In this study, the online learning readiness of 409 EFL learners at the university level in different parts of Türkiye was identified using the questionnaire by Hung et al. (2010), adapted to the Turkish context by İlhan and Çetin (2013). The (in)efficiency of online learning was explored by interviewing 40 EFL learners about their experiences before and after taking online English courses. Results indicated that learners seemed relatively ready for online education. However, they reported several factors for the inefficiency of online learning, such as a lack of real class environment and technical problems, for efficiency, such as learning in the comfort of their homes and having more time for self-development. They also mentioned several challenges and provided some suggestions for improving online learning.
Keywords: Learner readiness; efficiency of learning; online education; higher education; EFL learners